PENGARUH BELANJA BARANG DAN BELANJA MODAL TERHADAP PENYERAPAN ANGGARAN PADA SATUAN KERJA DIREKTORAT JENDERAL KEKAYAAN NEGARA PERIODE TAHUN 2023 - Mulyanti, khairaningrum; Khotimah, Sitti Hosnul (Universitas Logistik dan Bisnis Internasional, 2025)
Expenditures in public sector agencies need to be carried out effectively to minimize the potential for fraud. In order to increase budget absorption, public sector agencies need to allocate an adequate budget ceiling. Purposive sampling was used as a sampling technique and 86 DJKN work units were obtained that met the criteria in 2023. A two-tailed test was used as a hypothesis test and the data was analyzed using descriptive statistical analysis, normality test, multiple correlation analysis, multiple linear regression analysis, coefficient of determination, t test, and f test. The t test results show that goods expenditure or capital expenditure has a significant effect on budget absorption. The results of the f test show that goods expenditure and capital expenditure have a significant effect on budget absorption with a coefficient of determination value of 63.40%.